IMPLIKASI PELAKSANAAN LOMBA LINGKUNGAN UNTUK MENINGKATKAN PARTISIPASI DAN PEMBERDAYAAN MASYARAKAT DALAM PEMBANGUNAN DESA TEMPURAN DEMAK - Solikhatun, Is; Kusumawati, Dyah (JAB (Jurnal Akuntansi & Bisnis), 2021)
The purpose of this study was to describe the involvement of the people of Tempuran Village in realizing village achievement through village competitions. Village competition which is a village government program activity for the evaluation of the government under it which refers to article 5 Permendagri No. 66 of 2007. This research uses a qualitative approach with the type of case study research. This research data obtained by data collection techniques by observation, interviews, and documentation. The informants in this study were: Village Head, Village Secretary, Village RT / RW Management, Tempuran Village Community, Demak District, Demak Regency. Data analysis is carried out by examining all data from various sources, reducing data, categorization, checking the validity of the data, interpreting data, drawing conclusions and verification. The results of the study can be concluded that the programs and activities that exist in the competition winners can make a possibility of situations and conditions to improve village development, through various initiatives in smoothing and streamlining activities, policies, suggestions and local wisdom.Keywords: Community Participation and Empowerment, Environmental Competition, Development.